Gender-Based Impact of Epidermal Growth Factor Receptor Mutation in Patients With Nonsmall Cell Lung Cancer and Previous Tuberculosis. Issue 4 (January 2015) - Chang, Chia-Hao; Lee, Chih-Hsin; Ho, Chao-Chi; Wang, Jann-Yuan; Yu, Chong-Jen; Zhang., Yong
<x xml:space="preserve">Abstract</x> Abstract The association between tuberculosis (TB) and lung cancer is well known. However, carcinogenesis of TB and its connection with epidermal growth factor receptor (EGFR) mutation remains unclear. This study aimed to determine this connection to see if TB can affect the outcome of patients with lung cancer. This is a retrospective cohort study of patients with lung cancer receiving EGFR-tyrosine kinase inhibitors (TKIs) between 1996 and 2010 using the National Health Insurance Research Database of Taiwan. Because therapeutic response was required to apply EGFR-TKIs for >90 days, only patients with a follow-up of >120 days were studied and a responder was defined as intake of EGFR-TKIs >90 days. Predictors of EGFR-TKI response and survival were identified using logistic and Cox regression analyses, respectively. There were 8265 patients analyzed, including 6073 (73.5%) EGFR-TKI responder and 2192 (26.5%) nonresponder. A history of TB was found in 1.2% and 1.8% of the 2 groups, respectively. Comparing to male with pulmonary TB history, female with or without pulmonary TB history and male without pulmonary TB history all had a better EGFR-TKI response and 1-year progression-free survival (PFS). Gender and TB history were not independent prognostic factors of 2-year overall survival. The findings were similar in the subpopulation without chronic obstructive pulmonary disease, malignancies other than lung cancer, and low-income status. TB has a gender-dependent impact, with better EGFR-TKI response and 1-year PFS in female patients with lung cancer. The carcinogenesis and inflammation of TB may be different between genders.